Mindfulness-Based Cognitive Therapy terhadap Penurunan Kecemasan pada Pasien Kanker - Legu, Ermelinda Toyo; Gayatri, Dewi; Waluyo, Agung (Journal of Telenursing (JOTING), 2024)
This research aims to determine the effectiveness of mindfulness-based cognitive therapy in reducing anxiety in cancer patients. The research method used is a systematic review, searching articles in six trusted databases: ProQuest, EBSCOhost, PubMed, Wiley Online Library, SpringerLink, and Google Scholar—article analysis using the PRISMA method. The research results show that mindfulness-based cognitive therapy can reduce anxiety in cancer patients. In conclusion, apart from reducing stress, mindfulness-based cognitive therapy can also reduce fatigue, reduce fear of recurrence, reduce depression, and improve the quality of life of cancer patients.This research aims to determine the effectiveness of mindfulness-based cognitive therapy in reducing anxiety in cancer patients. The research method used is a systematic review, searching articles in six trusted databases: ProQuest, EBSCOhost, PubMed, Wiley Online Library, SpringerLink, and Google Scholar—article analysis using the PRISMA method. The research results show that mindfulness-based cognitive therapy can reduce anxiety in cancer patients. In conclusion, apart from reducing stress, mindfulness-based cognitive therapy can also reduce fatigue, reduce fear of recurrence, reduce depression, and improve the quality of life of cancer patients. Keywords: Anxiety, Mindfulness-Based Cognitive Therapy, Cancer Patients